2019
DOI: 10.1057/s41284-019-00211-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of crime facilitated by the consumer Internet of Things

Abstract: The nature of crime is changing -estimates suggest that at least half of all crime is now committed online. Once everyday objects (e.g. televisions, baby monitors, door locks) that are now internet connected, collectively referred to as the Internet of Things (IoT), have the potential to transform society, but this increase in connectivity may generate new crime opportunities. Here, we conducted a systematic review to inform understanding of these risks. We identify a number of high-level mechanisms through wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
1
19
0
2
Order By: Relevance
“…For example, research has shown that-by taking advantage of hardware or protocol flaws-attackers can exploit man-in-the-middle attacks to intercept communications from and to wearable devices to steal personal information, invading user's privacy and exposing them to the risk of identity theft [7]. Attackers can also take advantage of the weak authentication and encryption protocols used in many cameras enabling them to eavesdrop on camera streams [8], again raising privacy concerns and creating opportunities for crime [9]. Such concerns may impede consumer confidence in, and the uptake of, the benefits the IoT promises to deliver [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that-by taking advantage of hardware or protocol flaws-attackers can exploit man-in-the-middle attacks to intercept communications from and to wearable devices to steal personal information, invading user's privacy and exposing them to the risk of identity theft [7]. Attackers can also take advantage of the weak authentication and encryption protocols used in many cameras enabling them to eavesdrop on camera streams [8], again raising privacy concerns and creating opportunities for crime [9]. Such concerns may impede consumer confidence in, and the uptake of, the benefits the IoT promises to deliver [4].…”
Section: Introductionmentioning
confidence: 99%
“…While systematic reviews are generally used to synthesise findings about existing or historic issues in an unbiased way, the approach has a substantial value in helping to identify and organise material about future issues [40], in this case crimes that might be facilitated by biotechnology, synthetic biology and genetic engineering. The aim of the review proposed here is to identify what is and what is not known about these issues to guide future research in this field and to identify potential policy implications.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to assess the quality of the evidence of an event happening (i.e., crime type), when it has not happened yet (i.e., emerging crime type). A recently published systematic review shares this difficulty [40]. Moreover, it is expected that the extracted studies will consist of both quantitative and qualitative study designs.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Typically, SRs are conducted to synthesize evidence on “what works” in fields such as medicine (Curtis and Cairncross, 2003 ) where data are plentiful. However, SRs are also useful where data are more fragmented and for emerging issues, such as new crime trends, where they can help summarize the state-of-the-art, assess the quality of the existing research, identify gaps in knowledge and encourage further work, where needed (Blythe and Johnson, 2019 ). Here, four objectives were pursued, to synthesize the evidence on:…”
Section: Introductionmentioning
confidence: 99%